Perbandingan Penghasilan Antara Petani Tembakau Rajang Serta Padi Sebagai Tanaman Rotasi di Dusun Krajan Desa Gesikan Kecamatan Gondang Kabupaten Tulungagung - Asbitatul Kusna Devi; Wiwiek Andajani; Widi Artini (JINTAN : Jurnal Ilmiah Pertanian Nasional, 2022)
Along with household needs, farmers are required to have additional income. One way to overcome the income constraints is through a crop rotation system. Chopped tobacco and rice are crops that can be rotated. These two crops have been planted by farmers in the Krajan Hamlet, Gesikan Village, TuIungagung Regency. This study aimed to determine the costs and revenues of crop rotation farming of chopped tobacco and rice in the location. The sampling method used in this research was the census. Based on the survey results and these criteria, the total number of farmers was 25 people. Meanwhile, the types of data used in this research were primary and secondary data. The analytical methods used included cost, revenue, and income analysis. Comparative analysis of income using t-test. The results of the research showed that the total average production cost of tobacco farming was IDR48,840,304/ha, which was greater than the production cost of rice farming, which was IDR25,334,347, while the average total revenue for tobacco farming was IDR 80,550,000/ha. Meanwhile, the income of rice farming was IDR33.237.000/ha and the average income from tobacco farming was IDR31.709.696/ha. The result of hypothesis testing shows that the t-count value was 1.697260887, which was less than t-table 15.95651376. Therefore, the income from tobacco farming was higher than the income from rice farming statistically.